To find which equation has a solution of -2, we can substitute -2 into each equation and see if the equation holds true.
A: \(7 + x = 5\)
Substituting -2 for \(x\):
\[
7 + (-2) = 5 \implies 5 = 5 \quad \text{(True)}
\]
B: \(3x = -12\)
Substituting -2 for \(x\):
\[
3(-2) = -12 \implies -6 = -12 \quad \text{(False)}
\]
C: \(-6 - x = 20\)
Substituting -2 for \(x\):
\[
-6 - (-2) = 20 \implies -6 + 2 = 20 \implies -4 = 20 \quad \text{(False)}
\]
D: \(8 = 3 - x\)
Substituting -2 for \(x\):
\[
8 = 3 - (-2) \implies 8 = 3 + 2 \implies 8 = 5 \quad \text{(False)}
\]
The only equation that has a solution of -2 is A: \(7 + x = 5\).